Clinical Outcomes and Progression to Orthopedic Surgery in Juvenile‐ Versus Adult‐Onset Ankylosing Spondylitis. Issue 5 (May 2015) - Jadon, Deepak R.; Shaddick, Gavin; Jobling, Amelia; Ramanan, Athimalaipet V.; Sengupta, Raj
<x xml:space="preserve">Abstract</x> Objective Juvenile‐ and adult‐onset ankylosing spondylitis (AS) are subtypes of AS that may have different clinical outcomes. We compared cohorts of juvenile‐onset AS and adult‐onset AS in terms of clinical characteristics, clinical outcomes, proceeding to AS‐related orthopedic surgery, and type of orthopedic surgery. Methods A retrospective cohort study was conducted of all AS patients attending a teaching hospital. Demographics, clinical parameters, and history of AS‐related orthopedic surgery to the spine, root, or peripheral joints were recorded. Differences between surgery for juvenile‐ and adult‐onset AS patients, and effects of covariates were assessed using logistic regression and survival analyses. Results A total of 553 AS patients were studied: 162 juvenile‐onset AS and 391 adult‐onset AS cases. After adjusting for significant covariates, adult‐onset AS cases were less likely to proceed to surgery (odds ratio [OR] 0.31, P < 0.001), have a hip procedure (resurfacing or arthroplasty; OR 0.374, P = 0.001), and have hip arthroplasty (OR 0.43, P = 0.01). Significant differences were also observed when comparing Kaplan‐Meier survival curves (P = 0.001) and using Cox proportional hazards regression (P = 0.002). A history of smoking was not associated with surgery. AS cases with older age at symptom onset were far less likely to have surgery than those with younger onset, in a nonlinear manner. Conclusion Juvenile‐onset AS cases are more likely than adult‐onset AS cases to proceed to hip arthroplasty, but equally likely to have hip resurfacing and hip arthroplasty revision/re‐revisions. Smoking was not associated with the risk of orthopedic surgery. Orthopedic surgery was unlikely after 40 years of disease in both subsets.